PENGARUH GAYA KEPEMIMPINAN DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI DAN DAMPAKNYA TERHADAP KUALITAS PELAYANAN MASYARAKAT DI WILAYAH KECAMATAN GADINGREJO KOTA PASURUAN - Eko Yulianto; Nasharuddin Mas; Muchlis Mas’ud (Bajang Institute, 2025)
The purpose of this study is to analyze and empirically test the influence of leadership style and work motivation on employee performance and its impact on the quality of public services in the Gadingrejo District, Pasuruan City. This type of research is a correlational study, namely research that aims to identify the relationship between two or more variables. The research approach used in this study is a quantitative approach. In this study, the population is grouped into two categories based on its characteristics, namely: The Gadingrejo District employee group, Pasuruan City, totaling 75 people, and the service user community group in Gadingrejo District, Pasuruan City, which at the time of the study (data collection) the number is not known with certainty (undefined population). Determination of the number of samples for the Gadingrejo District employee group, Pasuruan City used saturated sampling. Determination of the number of samples for the service user community group in Gadingrejo District, Pasuruan City used a sampling quota, which was set at 75 people which was based on the same as the number of samples of the first group (employee group) in order to make it easier to analyze the data. The data analysis technique used in this study is Partial Least Square-Structural Equation Modeling (PLS-SEM) using smartPLS software version 4. Research conclusion: Leadership style does not have a positive and significant effect on the quality of public services. Leadership style has a positive and significant effect on employee performance. Employee work motivation has a positive and significant effect on the quality of public services. Employee work motivation has a positive and significant effect on employee performance. Employee performance has a positive and significant effect on the quality of public services. Leadership style has a positive and significant effect on the quality of public services through employee performance as a mediator and is full mediated. Employee work motivation has a positive and significant effect on the quality of public services through employee performance as a mediator and is partially mediated.